Controlled growth of biosynthetic nanowires - Nguyen, Han N. (Tufts University. Tisch Library., 2017)
Biosynthetic materials, assembled from natural building blocks, provide great potential to overcome the limitations posed by conventional materials. When used in platforms that require interface with biological systems, traditional electronic probes made out of metal or semiconductors are chemically and mechanically incompatible, leading to constrained biomedical applications. Employing the fact that certain types of bacteria, such as Shewanella and Geobacter, produce conductive filamentous pilli, or “nanowires”, to facilitate electron transport under electron acceptor limited condition, this research aims to achieve controlled growth of these biosynthetic nanowires and harvest them to use as building blocks for several applications. Key to the overall research design is defining/immobilizing exoelectrogenic bacteria and electron acceptors in a spatially controlled manner, so that the growth of protein nanowires as interconnections can be rationally programmed. I am currently developing several methods to accomplish this goal: (1) calcium-crosslinked alginate beads, where microfluidic device is utilized to encapsulate bacteria and electron acceptors in separate beads; (2) microcontact printing of polydopamine as cell-adhesion molecules for 2D bacteria patterning; and (3) stereolithography-based photopolymerization. I will further optimize the bacteria culture conditions that facilitate the growth of conductive nanowires, and develop approaches to non-invasively isolate high-purity nanowires from the bacteria’s bodies. These toxin-free nanowires can then be individually tested, integrated, and exploited as interfacing components in various bioelectronic probe designs. Current research has the potential to bridge the gap between living systems and artificial electronics and bring forth many advancements and revolutions in related fields.